2017
DOI: 10.2147/cia.s135390
|View full text |Cite
|
Sign up to set email alerts
|

Applications of direct-to-consumer hearing devices for adults with hearing loss: a review

Abstract: BackgroundThis systematic literature review is aimed at investigating applications of direct-to-consumer hearing devices for adults with hearing loss. This review discusses three categories of direct-to-consumer hearing devices: 1) personal sound amplification products (PSAPs), 2) direct-mail hearing aids, and 3) over-the-counter (OTC) hearing aids.MethodA literature review was conducted using EBSCOhost and included the databases CINAHL, MEDLINE, and PsycINFO. After applying prior agreed inclusion and exclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 25 publications
0
60
0
Order By: Relevance
“…Such an approach to combine appropriate technology with a local support base is essential to meet the needs of LMIC, as there is a chronic shortage of trained support personnel for hearing aids [31,40] The LoCHAid represents an opportunity to change the value proposition of hearing aids. In European countries such as the United Kingdom, where hearing aids are fully or partially covered under governmental health programs such as National Health Service, uptake remains low at 30% too [8,13,34]. Social stigma is one of the barriers; however, that may be changing with the arrival of an aging population that has grown more comfortable with technology and have a desire for more fashionable, robust, and better hearing technology [1,34].…”
Section: Coupler Gain Simulations Using the Speechmap Testmentioning
confidence: 99%
See 2 more Smart Citations
“…Such an approach to combine appropriate technology with a local support base is essential to meet the needs of LMIC, as there is a chronic shortage of trained support personnel for hearing aids [31,40] The LoCHAid represents an opportunity to change the value proposition of hearing aids. In European countries such as the United Kingdom, where hearing aids are fully or partially covered under governmental health programs such as National Health Service, uptake remains low at 30% too [8,13,34]. Social stigma is one of the barriers; however, that may be changing with the arrival of an aging population that has grown more comfortable with technology and have a desire for more fashionable, robust, and better hearing technology [1,34].…”
Section: Coupler Gain Simulations Using the Speechmap Testmentioning
confidence: 99%
“…In low-and middle-income countries (LMIC), hearing aid adoption rates are below 3% whereas in non-LMIC countries, the adoption rate is around 20% [1]. Various reasons (e.g., self-reported hearing disability, access to hearing healthcare) may contribute to this poor uptake [8]; however, cost is one of the most substantial factors [8][9][10][11][12][13][14]. The retail price of a pair of hearing aids range between $1,000 (low-end) to $8,000 (highend), with an average price being $4,700 in the United States [7,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, they found that along with the usual problems of hearing aids, such as the stigma associated with wearing them, there were significant audio feedback issues limiting use beyond certain levels of hearing loss. 28,29 Identifying the gap in the hearing loss population allowed Earlens to invent a solution that amplifies sound through light and, therefore, avoid traditional hearing aid feedback issues. …”
Section: Understanding the Disease State And Existing Solutionsmentioning
confidence: 99%
“…47 In addition, acceptance and uptake of hearing aids have been demonstrated to be poor. 28 Many patients note that there is a stigma to using hearing aids and that while hearing aids provide some hearing benefit, the technology has limitations in terms of feedback and frequency range. The scope of this problem is large, and while there are currently alternative solutions, e.g., traditional hearing aids, to help these patients, this problem represents the origins of a clinical need.…”
Section: Needs Statementmentioning
confidence: 99%